2004
DOI: 10.1073/pnas.0403456101
|View full text |Cite
|
Sign up to set email alerts
|

Functional variants within the secreted frizzled-related protein 3 gene are associated with hip osteoarthritis in females

Abstract: Osteoarthritis (OA) is a leading cause of disability in Western society with multiple risk factors, including a complex genetic pattern. Identifying loci involved in the heredity of OA might lead to insights into the molecular pathogenesis of this common disorder. A previous genome scan mapped a primary hip OA susceptibility locus to chromosome 2q with a maximum multipoint logarithm of odds score of 1.6 in 378 affected sibling pair families. Here, microsatellite targeting of eight candidate genes in this regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
307
3
8

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 364 publications
(325 citation statements)
references
References 36 publications
7
307
3
8
Order By: Relevance
“…However, the present study is, to our knowledge, the first to show a genetic association with knee OA. We must note that some of the subjects used in the current study (the 185 female control subjects from Oxford) are shared between this study and the original study by Loughlin et al (8). For this reason, the 2 studies are not totally independent.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the present study is, to our knowledge, the first to show a genetic association with knee OA. We must note that some of the subjects used in the current study (the 185 female control subjects from Oxford) are shared between this study and the original study by Loughlin et al (8). For this reason, the 2 studies are not totally independent.…”
Section: Discussionmentioning
confidence: 92%
“…Accelerated cartilage breakdown has been shown to develop in knockout mice deficient in this gene (7). The original study in which an association of FRZB with hip OA was reported involved a cohort of women (8); that study showed that the associated alleles at FRZB reduced the activity of the protein encoded. In particular, the haplotype composed of substitutions at 2 highly conserved aspartic acid residues in FRZB (R200W and R324G) was highlighted as a strong risk factor for primary hip OA.…”
mentioning
confidence: 99%
“…Recently, the Wnt/␤-catenin signaling cascade, which is involved in skeletal and joint development, has received attention in OA (3,4). The potential role of the Wnt signaling pathway in the development of OA has been suggested by the increase in susceptibility for hip OA in women that is associated with 2 functional genetic variants in FRZB, which encodes Frizzled-related protein (FRP) (5)(6)(7)(8). Secreted FRP (sFRP) is a naturally occurring soluble antagonist that competitively binds Wnt to antagonize its ability to signal through Frizzled receptors (9,10).…”
mentioning
confidence: 99%
“…Secreted FRP (sFRP) is a naturally occurring soluble antagonist that competitively binds Wnt to antagonize its ability to signal through Frizzled receptors (9,10). FRP is expressed in adult human cartilage, and its messenger RNA expression is altered in response to cartilage injury in vitro and in vivo (8,11), suggesting that FRP might protect against the development or progression of OA.…”
mentioning
confidence: 99%
“…35 The associations reported in the original paper were marginal. 36 When multiple testing is considered, only a negative association has been reported in replication studies, even in the European Caucasians. 13,37,38 We also did not find an association of the FRZB variants in the Japanese and Han Chinese populations (D Shi et al, unpublished data).…”
Section: Gdf5mentioning
confidence: 99%